Wellness Program Counsel (International Journal of Engineering and Computer Science, 2018)
Internet of Things (IoT) is a new technological paradigm that can connect things from various ﬁelds through the Internet. Smart healthcare will be the most dominant Internet of Things (IoT) application. The adoption of information and communication technologies (ICT) within the healthcare sector led to the concept of electronic health (e-health), which is contributing to reduced costs and increased efficiency. E-Health systems depending on a modern technology play a vital role in eradicating the problems and faster curing of the patients. Also, a lot of advancement has been done in order to improve the systems in various terms of size, speed mobility and faster communication in emergency situations. Sensor data getting Activity from blue-tooth.  New smart health monitoring systems have proved to be of great help to the healthcare of the patients. But the major constraint of this system is that patients are supposed to be bed fitted and kept in the smart rooms and are immobile.